Novel Application of Nanofluidic Chip Digital PCR for Detection of African Swine Fever Virus - Jia, Rui; Zhang, Gaiping; Liu, Hongliang; Chen, Yumei; Zhou, Jingming; Liu, Yankai; Ding, Peiyang; Wang, Yanwei; Zang, Weimin; Wang, Aiping (Frontiers in Veterinary Science, 2021)
African swine fever virus (ASFV) gives rise to a grievous transboundary and infectious disease, African swine fever (ASF), which has caused a great economic loss in swine industry. To prevent and control ASF, once suspicious symptoms have presented, the movement of animal and pork products should be stopped, and then, laboratory testing should be adopted to diagnose ASF. A method for ASFV DNA quantification is presented in this research, which utilizes the next-generation PCR platform, .nanofluidic chip digital PCR (cdPCR). The cdPCR detection showed good linearity and repeatability. The limit of detection (LOD) for cdPCR is 30.1995 copies per reaction, while no non-specific amplification curve was found with other swine viruses. In the detection of 69 clinical samples, the cdPCR showed significant consistency (91.30% (63/69)) to the OIE approved qPCR.. Compared to the commercial qPCR kit, the sensitivity of the cdPCR assay was 86.27% (44/50) and the specificity was 94.44% (17/18). The positive coincidence rate of the cdPCR assay was 88% (44/50). The total coincidence rate of the cdPCR and kit was 89.86% (62/69) and the kappa value reached to 0.800 (P < 0.0001). This is the first time that cdPCR has been applied to detecting ASFV successfully.